Detection of Mutations in Exon 8 of TP53 by Temperature Gradient 96-Capillary Array Electrophoresis - A. Torgunrud Kristensen; J. Bjørheim; M. Minarik; K.-E. Giercksky; P.O. Ekstrøm (BioTechniques)
Various capillary electrophoresis applications have increasingly been utilized in mutation detection. Separation of two species is either based on secondary structure or differences in melting of DNA due to the mutation. Detection of the mutant is based on its mobility difference in the sieving matrix. We have adapted a regular 96-capillary sequencing instrument, the MegaBACETM 1000, for mutation detection based on thermodynamic stability and mobility shift during electrophoresis. Denaturation of the lower melting domain of the DNA was achieved with a gradually decreasing temperature gradient in combination with a chemical denaturant. Samples were analyzed for mutants in exon 8 of the TP53 gene from tumor samples and controls. Genomic DNA was PCR-amplified with one fluorescein labeled primer and one GC-clamped primer, diluted in water, and analyzed by temperature gradient 96-capillary array electrophoresis. Tumor samples and PCR reconstruction experiment samples were resolved by capillary gel electrophoresis under appropriate temperature gradient denaturing conditions. Ninety-six samples were analyzed in one run, with an analysis time of 30 min and a sensitivity to detect mutated alleles in wild-type background down to 0.4%. The technique proved to be robust, in that the gradient compensates for temperature differences within the capillary chamber; thus, each capillary will pass through the optimal separating conditions around the theoretical melting temperature for TP53 exon 8, separating homoduplexes and heteroduplexes. This technique is applicable to any sequence previously analyzed by DNA melting gel techniques or sequences harboring iso-melting domains of 100–V120 bp.